Paleomagnetism of the Late Precambrian Fourchu Group, Cape Breton Island, Nova Scotia - Johnson, Rex J. E.; Voo, Rob Van der (Canadian Journal of Earth Sciences, 1986)
Volcanogenic sediments of the Fourchu Group and a gabbroic intrusion, which are found in the Avalonian terrane of south-eastern Cape Breton Island, have been sampled for paleomagnetic analysis. Upon detailed thermal and alternating-field demagnetization, three often-superimposed components of magnetization are obtained. One of these is aligned with the present-day geomagnetic field direction in Nova Scotia and is assumed to be of recent origin. The second group of directions is south-southeasterly and shallow, is postfolding in age, and is inferred to represent a Carboniferous overprint. The third direction, carried almost always by hematite, is also postfolding and yields a dual-polarity mean direction to the northwest or south-east, with a fairly steep inclination (D = 132°, I = −63°). This last direction is not seen in Avalonian or other North American rocks of Devonian or younger age; it is, therefore, bracketed in age between the earliest folding of the rocks and the latest Silurian. Given that Taconic folding has not been reported for this area, we assume that this magnetization was introduced in the rocks during uplift and oxidation after an Avalonian folding phase. For the Avalon terrane of Nova Scotia, the available paleomagnetic data reveal a set of moderately high paleolatitudes for the Late Precambrian and early Paleozoic, in contrast to the near-equatorial values predicted for the area under the assumption that it remained fixed with respect to the craton. On the other hand, strong similarities exist between Avalonian paleolatitudes and those for Armorica and Gondwana; a tentative reconstruction is proposed in which Avalon is adjacent to Armorica and Gondwana in the Late Precambrian and early Paleozoic.